2021
DOI: 10.1021/acssuschemeng.1c01156
|View full text |Cite
|
Sign up to set email alerts
|

Structural Effectiveness of AgCl-decorated Ag Nanowires Enhancing Oxygen Reduction

Abstract: In anion exchange membrane fuel cells (AEMFCs) for green energy, silver (Ag)-based compounds are promising non-Pt electrocatalysts with high catalytic activity and a low cost for the oxygen reduction reaction (ORR). Although silver chloride (AgCl) shows high catalytic activity due to the ligand effect originating from the electronegativity difference between the two elements, its low electroconductivity remains a significant issue. Here, we report Ag-AgCl core–shell nanowires decorated with AgCl (AgCl-Ag@AgCl … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
19
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 20 publications
(20 citation statements)
references
References 47 publications
1
19
0
Order By: Relevance
“…The immersed CMO, NMO, and MMO powders are thoroughly dried for the XPS testing, and compared with the pristine samples. Mo in the pristine molybdate oxides resides in the oxidation state of Mo (VI) with a pair of Mo 3d 5/2 (232.31–232.63 eV) and Mo 3d 3/2 peaks, [ 45–47 ] with a slight difference in binding energy due to the discrepancies of surficial element compositions (Figure 4c–e). And Co, Ni, and Mn are all divalent (Figure S8, Supporting Information).…”
Section: Resultsmentioning
confidence: 99%
“…The immersed CMO, NMO, and MMO powders are thoroughly dried for the XPS testing, and compared with the pristine samples. Mo in the pristine molybdate oxides resides in the oxidation state of Mo (VI) with a pair of Mo 3d 5/2 (232.31–232.63 eV) and Mo 3d 3/2 peaks, [ 45–47 ] with a slight difference in binding energy due to the discrepancies of surficial element compositions (Figure 4c–e). And Co, Ni, and Mn are all divalent (Figure S8, Supporting Information).…”
Section: Resultsmentioning
confidence: 99%
“…26 Choi et al also presented that the conductivity of AgCl could be improved by using Ag nanowires as a core structure which had a positive impact on the catalytic activity. 27 Herein, we report a superior ORR activity of the Ag/AgCl nanostructures derived from the selective dealloying of AgCu alloy NPs in the acidic solution. It was found that the nal structural phase that exhibited the best ORR activity depended strongly on initial AgCu alloy compositions and Cu dealloying process parameters, indicating that multiple steps must be followed.…”
Section: Introductionmentioning
confidence: 96%
“…26 Choi et al also presented that the conductivity of AgCl could be improved by using Ag nanowires as a core structure which had a positive impact on the catalytic activity. 27…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, several approaches have been proposed to reduce the usage of precious PGMs while maintaining high catalytic performance. [5][6][7][8][9][10][11][12] Recently, graphenesupported single-atom catalysts (G-SACs) have been demonstrated to be one of the best of these strategies because G-SACs not only decrease the amount of loaded precious metal but also improve the mass activity by maximizing the atomic efficiency with high product selectivity. 2,3,13,14 However, G-SACs always face stability issues owing to the high chemical potential of single atoms, particularly agglomeration and dissolution.…”
Section: Introductionmentioning
confidence: 99%